PENERTIBAN REKLAME DI KOTA PEKANBARU - Viola Fitriani Br. Daulay; Zaili Rusli (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
With the rapid development of the city and in accordance with the high rate of growth of various advertisements, it is necessary to arrange the implementation of advertisements in an integrated, comprehensive, effective and efficient manner. The control of billboards in Pekanbaru City is regulated in Pekanbaru Mayor Regulation Number 24 of 2013 concerning the Implementation of Advertisements, the aim is to create an orderly billboard in Pekanbaru City in the context of directed and controlled urban spatial planning. However, in reality there are still problems in controlling illegal billboards in Pekanbaru City. The purpose of this research is to find out how to control billboards in Pekanbaru City and the inhibiting factors that affect the implementation of controlling billboards in Pekanbaru City. This study uses the theory of Bohari (1992:25) Repressive/Direct Supervision with indicators of periodic supervision, control/reprimand, sanctions. This study uses a qualitative research method with a descriptive approach, the required data such as primary data and secondary data obtained through purposive sampling data collection techniques used, namely, literature study, interviews, documentation analysis, observation. The results showed that the supervision of controlling billboards in Pekanbaru City had not run optimally, while the inhibiting factors in controlling billboards were the absence of Coordination SOPs between related agencies, and the weak commitment of the billboard control task force team in controlling billboards in Pekanbaru City.